Open Source Software Superstream Series Java - Hightower, Kelsey; Ruiz, Ixchel; Marks, Stuart; Parlog, Nicolai; Cummins, Holly; Gee, Trisha; Subramaniam, Venkat; Hoffmann, Marc; Goetz, Brian (O'Reilly Media, Inc., 2021)
Java's been around for over a quarter of a century now, but it remains dominant in the world of programming due to its portability, speed, and security. Yet with today's increased reliance on cloud computing and distributed systems, the language must keep changing to keep pace. In this Superstream event, Java Champions and other experts offer perspectives on topics from concurrency to functional programming, giving insight into how Java is keeping up with the cloud and beyond.